Gender – Based Violence in Chao Te-Yin’s Nina Wu (灼人秘密 ) Movie - I G A Putri Natalie Udayana; Ressi Maulidina Delijar (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2023)
Literature work is one of many creative mediums for an author in expressing their imagination. The imagination set forth in a literary work is closely related to the author's environment and social phenomena, together with the intrinsic and extrinsic elements of a literary work, these messages are made livelier so that they are more accepted by their respective audience. The social reflection raised in a literary work is often in the form of criticism of the author regarding an issue, using literary work to convey criticism regarding a social issue isn’t something unheard of, there are plenty of authors that did exactly that, and Chao Te - yin is no exception. Chao Te-Yin 《趙德胤》 or better known as Midi Z raises the issue of gender-based violence in the film industry through his movie titled Nina Wu《灼人秘密》. Using the mimetic approach paired with the descriptive qualitative method, the author conducts in-depth observations to collect data obtained through dialogue, and symbols presented in the movie.  By doing so, the author found that there are various forms of abuse or misconduct in the film industry namely psychological, emotional, physical, and sexual that severely impacted the victim’s mental well-being.